Madagascar's fire regimes challenge global assumptions about landscape degradation. (18th May 2022) - Phelps, Leanne N.; Andela, Niels; Gravey, Mathieu; Davis, Dylan S.; Kull, Christian A.; Douglass, Kristina; Lehmann, Caroline E. R.
Abstract: Narratives of landscape degradation are often linked to unsustainable fire use by local communities. Madagascar is a case in point: the island is considered globally exceptional, with its remarkable endemic biodiversity viewed as threatened by unsustainable anthropogenic fire. Yet, fire regimes on Madagascar have not been empirically characterised or globally contextualised. Here, we contribute a comparative approach to determining relationships between regional fire regimes and global patterns and trends, applied to Madagascar using MODIS remote sensing data (2003–2019). Rather than a global exception, we show that Madagascar's fire regimes are similar to 88% of tropical burned area with shared climate and vegetation characteristics, and can be considered a microcosm of most tropical fire regimes. From 2003–2019, landscape‐scale fire declined across tropical grassy biomes (17%–44% excluding Madagascar), and on Madagascar at a relatively fast rate (36%–46%). Thus, high tree loss anomalies on the island (1.25–4.77× the tropical average) were not explained by any general expansion of landscape‐scale fire in grassy biomes. Rather, tree loss anomalies centred in forests, and could not be explained by landscape‐scale fire escaping from savannas into forests. Unexpectedly, the highest tree loss anomalies on Madagascar (4.77×) occurred in environments without landscape‐scale fire, where the role of small‐scale fires (<21 h [0.21 km 2 ]) is unknown. While landscape‐scale fire declined across tropical grassy biomes, trends in tropical forests reflected important differences among regions, indicating a need to better understand regional variation in the anthropogenic drivers of forest loss and fire risk. Our new understanding of Madagascar's fire regimes offers two lessons with global implications: first, landscape‐scale fire is declining across tropical grassy biomes and does not explain high tree loss anomalies on Madagascar. Second, landscape‐scale fire is not uniformly associated with tropical forest loss, indicating a need for socio‐ecological context in framing new narratives of fire and ecosystem degradation. Abstract : Narratives of landscape degradation and forest loss often centre on unsustainable fire use by local communities. On Madagascar – a global biodiversity hotspot with high rates of forest loss – relationships between fire, vegetation and people are poorly understood. By comparing Madagascar to the global tropics, we found that the island's five fire regimes were similar to 88% of tropical burned area, and high tree loss anomalies were centred in environments without landscape‐scale fire (>0.21km2). Rather than explaining Madagascar's high degradation rates, landscape‐scale fire declined across tropical grassy biomes and was not a uniform indicator of forest loss, with global implications.